Corrosion Behavior of Galvanized Steel Embedded in Concrete Exposed to Soil Type MH Contaminated With Chlorides - Baltazar-Zamora, Miguel Angel; Mendoza-Rangel, José Manuel; Croche, René; Gaona-Tiburcio, Citlalli; Hernández, Cindy; López, Luis; Olguín, Francisco; Almeraya-Calderón, Facundo (Frontiers in Materials, 2019)
The behavior of corrosion in reinforced concrete, buried in a soil type silt of higher plastic (MH), the present study represents the conditions of exposure that can find the foundations of infrastructure such as bridges, buildings, pavements, when in contact with a soil that could contain aggressive agents like chlorides and sulfates. In such concrete specimens a carbon steel bar AISI 1018 and Galvanized Steel was embedded as reinforcement, the mixed concrete was of ratio water/cement (w/c) = 0.45 (compressive strength, f'c = 350 kg/cm2), according to ACI 211.1, using cements Portland Cement Composite [CPC 30R (Type I) and CPC 30R RS (Type V)]. The used electrochemical techniques such as Corrosion Potentials (ASTM C-876-15) and Linear Polarization Resistance. LPR (ASTM-G59). The specimens were buried in a soil type MH contaminated with 0, 1, 2, and 3 wt.% NaCl as aggressive agent by weight of soil, the exposure time was 260 days where, the results show that when the presence of NaCl in the soil was increased to 2 and 3% the levels of corrosion are from high to very high in all concretes, presenting a little better performance the concretes reinforced with galvanized steel and a small benefit could be identified or related to the properties of a denser and less impermeable matrix that presented the concrete mix made with cement CPC 30R RS.